Predictors of Secukinumab Treatment Response and Continuation in Axial Spondyloarthritis: Results From the EuroSpA Research Collaboration Network - Pons, Marion; Georgiadis, Stylianos; Hetland, Merete Lund; Faizy, Ahmadzay Zohra; Rasmussen, Simon; Christiansen, Sara N.; Di Giuseppe, Daniela; Wallman, Johan K.; Pavelk,a Karel; Závada, Jakub; Codreanu, Catalin; Glintborg, Bente; et al. (The Journal of Rheumatology, 2025)
Objective. In patients with axial spondyloarthritis (axSpA) initiating secukinumab (SEC), we aimed to
identify baseline (treatment start) predictors of achieving low disease activity (LDA) after 6 months, as
measured by the Axial Spondyloarthritis Disease Activity Score using C-reactive protein (ASDAS-CRP)
and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), as well as treatment continuation after
12 months.
Methods. From 11 European registries, patients with axSpA who initiated SEC treatment in routine care,
with available data on 6-month ASDAS-CRP and BASDAI assessments were included. Logistic regression
analyses on multiply imputed baseline data were performed; potential baseline predictors included demographic, diagnosis, lifestyle, clinical, and patient-reported variables.
Results. In a pooled cohort of 1174 patients with axSpA, 5 of 19 potential assessed variables were mutually predictive for achieving LDA by ASDAS-CRP and BASDAI: higher physician global assessment score, noncurrent smoking, lack of prior exposure to biologic/targeted synthetic disease-modifying antirheumatic drugs, and lower Health Assessment Questionnaire scores and BASDAI scores. Moreover, radiographic axSpA and CRP ≤ 10 mg/L were associated with achieving ASDAS-CRP LDA, and HLA-B27 positivity and history of psoriasis with achieving BASDAI LDA, whereas earlier time of secukinumab initiation (2015-2017) was associated with treatment continuation.
Conclusion. In this European real-world study of patients with axSpA initiating SEC, predictors of achieving
LDA by ASDAS-CRP and BASDAI at 6 months and remaining on treatment at 12 months included both
clinical, patient-reported, and lifestyle factors, underscoring the complex mechanisms of real-world drug
effectiveness